(untitled) - Ayres, Robert U. (New York, 1979)
The book is extremely interesting to read and will be very well received thoth by the general piblic and by futurist.
Keywords: Forecasting,Economic forecasting,Technological forecasting,Dự báo,Dự báo kinh tế,Dự báo công nghệ